The paradox of aid : When are "socially dominant" individuals attracted to work in aid organisations? : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University, Albany, New Zealand - Wishart-Leng, Bryony (Massey University, 2012)
This research examined whether certain international aid organisations may be inadvertently recruiting individuals with high Social Dominance Orientation, and thereby potentially perpetuating poverty and inequality. Principles are taken from social dominance and similarity-attraction theories to examine social dominance in aid organisations. In a between-subjects experiment, N = 62 participants had their hypothetical Job Pursuit Intentions measured for one of two aid organisations, depicted in organisational descriptions as having either predominantly hierarchy-enhancing (e.g., pay disparity between local and expatriate workers) or hierarchy-attenuating (e.g., equal pay) qualities, with all other organisational characteristics being held equal. Social Dominance Orientation was also measured. There are two key findings. Firstly, participants who were not at all interested in working in the aid industry had, on average, higher social dominance than participants who were interested (p = .05 and p = .01). Secondly, among the remaining n = 47 participants, there was a borderline significant interaction effect of individual social dominance and the portrayed social dominance in organisational recruitment message on Job Pursuit Intentions (p = .07). Specifically, those with relatively high individual Social Dominance Orientation scores reported, on average, lower intentions to pursue work with a hierarchy-attenuating organisation, compared to individuals who scored lower on Social Dominance Orientation, a result that was borderline statistically significant (F(1,18) = 3.70, p = .07). Findings indicate that, whilst individuals with low social dominance tendencies are more likely to pursue aid work, social dominance portrayed in organisational recruitment messages has the potential to impact on whether individuals higher versus lower pursue work with specific aid organisations. The potential for similarity-attraction during recruitment to reflect social dominance in aid organisations is discussed. Improvements to the methodology for future research are also discussed.
Keywords: Social dominance; Aid workers; Aid organisations